HUBUNGAN TINGKAT PENGETAHUAN DENGAN KETERAMPILAN PETUGAS DALAM PELAKSANAAN TRIAGE DI INSTALASI GAWAT DARURAT RSUD WATES - Martanti, Renny; Nofiyanto, Muhamat; Joko Prasojo, R.Anggono (Jurnal Media Ilmu Kesehatan, 2015)
Background: Triage is the process of determining the priority of patients? treatment based on these verity of their condition. Triage at the Emergency Room is needed to manage the flow of patients coming to the Emergency Room through the sorting of patients according to their critical condition. Staff doing triage are those who have got certificate of training on the management of emergency patients or Basic Trauma Cardiac Life Support (BTCLS). Staff must have good knowledge in implementing triage. Objectives: To identify knowledge and skills of staff in implementing triage and strength of correlation between level of knowledge with skills of staff in implementing triage. Methods: The studi was descriptive analytic with crossectional approach. Samples were purposively selected, consisting of 20 respondents. Data were obtained through questionnaire and observation sheet and analyzed using Kendall Tau. Results: The result of the studi showed the majority of staff had good knowledge (70%) and skills (85%).  The result of Kendall Tau test showed score of significance was 0.025 (sig<0.05) with correlation coefficient 0.450 which meant that strength of correlation between level of knowledge with skills in the implementation of triage was average. Conclusion: There was significant correlation between level of knowledge with skills of staff at the Emergency Room of Wates Hospital with average strength of correlation. Keywords: Knowledge, skills, triage